Effect of Ca selective chelator BAPTA as depressant on flotation separation of magnesite from dolomite - Yin, Wanzhong; Sun, Haoran; Hong, Jongsu; Cao, Shaohang; Yang, Bin; Won, Changdok; Song, Myongsong (Minerals engineering, 2019)
•For the flotation separation of magnesite from dolomite, BAPTA had few influence on the recovery of magnesite.•BAPTA acts on Ca sites of the dolomite surface to depress the adsorption of oleic acid on the surface of dolomite.•BAPTA prevented the precipitation of Ca on the surface of the magnesite. With the depletion of high-grade magnesite mineral resources, improving the grade of magnesite obtained from gangue minerals such as dolomite has been attracting considerable attention from the industry. However, it is difficult to achieve the effective separation of magnesite from dolomite because of their similar chemical and crystal properties. In this study, 1, 2-bis (o-aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid (BAPTA) was used as a depressant for dolomite to improve the separation of magnesite from dolomite. Microflotation tests of the single minerals and artificially mixed minerals using oleic acid as a collector were performed to evaluate the selective depression effect of BAPTA. The results indicated that the BAPTA depressant had a selective effect on dolomite, thereby suggesting that a magnesite grade of 87.5%, recovery of 95.8%, and CaO content of 3.8% can be achieved with a BAPTA dosage of 62.5 mg/L. The depression mechanism of BAPTA was investigated using zeta-potential measurements, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The results indicated that BAPTA was selectively adsorbed on the surface of dolomite. The selective depression effect can be attributed to the selective chelating formation of BAPTA on Ca rather than Mg, which not only adsorbed BAPTA decreasing the adsorption sites of oleic acid on the dolomite surface, but also prevented the precipitation of Ca on the surface of the magnesite.